Telehealth-delivered caregiver training for autism: Recent innovations - Pacione, Laura (Frontiers in Psychiatry, 2022)
Providing treatment to children with autism is a global health priority, and research demonstrates that caregivers can be trained in techniques to promote their child’s social interaction, communication, play, positive behavior and skills during play and everyday activities. These caregiver-mediated interventions have been shown to promote a number of positive outcomes in children with autism, as well as their caregivers. When provided by telehealth, data indicate that caregiver training is acceptable and feasible, and associated with similar positive outcomes as live face-to-face training. Telehealth innovations, which have accelerated during the COVID-19 era, have demonstrated advantages over in-person delivery of services in terms of cost effectiveness and increased accessibility, however, more research is needed on feasibility, acceptability and effectiveness for different populations in different contexts. This brief review will highlight recent caregiver skills training interventions for autism that have been successfully adapted for telehealth delivery. Telehealth interventions that are scalable, adaptable, caregiver-mediated, open-access, and delivered as part of a stepped care model, have the potential to address the global treatment gap for families of children with autism and other neurodevelopmental disabilities. Considerations relevant to the global scale-up of caregiver-mediated interventions will also be discussed. Increased financial investment in telehealth research, implementation of universal health coverage and meaningful involvement of people with autism in shaping research agendas to meet local needs can also contribute to reduced health disparities for children and adults with neurodevelopmental disabilities, including autism.